Pengaruh Return On Asset dan Dana Pihak Ketiga Terhadap Financing Deposit Ratio (Fdr) Perbankan Syariah di Indonesia Periode 2015-2019 - Hasna Hasna; Heksawan Rachmadi (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The purpose of the research is to examine the effect of Return On Assets (ROA) and Third Party Funds (DPK) on the Financing Deposit Ratio (FDR) of Islamic banking partially or simultaneously. The results of this study indicate that Return On Assets (ROA) and Third Party Funds (DPK) simultaneously affect the Financing Deposit Ratio (FDR) of Islamic banking and partially only Third Party Funds that affect the Financing Deposit Ratio (FDR) of Islamic banking in Indonesia while Return On Asset (ROA) has no effect.